Prenatal cranial MR findings in fetuses with suspected CMV infection: Correlation with postnatal outcome and differential diagnostic considerations. Issue 6 (27th July 2020) - Goergen, Stacy; Lim, Zhengjie; Clark, Jenni; Teoh, Mark; Humnabadkar, Kedar; Fahey, Michael; Giles, Michelle
Abstract: Purpose: To: (1) Evaluate intrauterine MRI (iuMRI) findings in fetuses with suspected cCMV and correlate these with final diagnosis(es). (2) Correlate iuMRI in cases of confirmed cCMV with clinical outcomes. Methods: Retrospective cohort of iuMRI referrals for suspected cCMV between 2010 and 2018. Confirmed cCMV defined as positive amniotic fluid or postnatal CMV polymerase chain reaction (PCR) test and excluded cCMV defined by negative postnatal PCR. Results: Twenty‐nine singleton fetuses had iuMRI for suspected cCMV (median gestation 28 weeks (IQR 24–32). No postnatal outcome ( n  = 6) and no cCMV ascertainment ( n  = 5) provided 18 cases for analysis. cCMV positive ( n  = 11): three fetal deaths occurred, one spontaneous and two terminations of pregnancy (TOP), one for microcephaly and one for extensive polymicrogyria; 4/ 8 survivors had normal US and iuMRI with normal newborn hearing screen (AABR)/ neurological examination; two had polymicrogyria and cerebral palsy (CP) GMFCS II and V; 1 had isolated ventriculomegaly and failed newborn AABR; 1 had ventriculomegaly with germinolytic cysts, normal AABR and development at 3/12. cCMV negative ( n  = 7): Germinolytic cysts were present in 4 cases with 2/4 also having callosal hypogenesis and postnatal genetic and clinical diagnosis of mitochondrial disorder. The third and fourth had a normal newborn metabolic screen and neurological examination. Three deaths were due to toxoplasmosis ( n  = 1), TOP for severe ventriculomegaly ( n  = 1) and bilateral schizencephaly ( n  = 1). Conclusions: Polymicrogyria in fetuses with cCMV, undetected with prenatal US, was associated with CP. Germinolytic cysts were non‐specific for cCMV and due to mitochondrial disorders when callosal hypogenesis was present.